Maternal temperature in emergency caesarean section (MATES): an observational multicentre study. (May 2021) - Thorburn, P.T.; Monteiro, R.; Chakladar, A.; Cochrane, A.; Roberts, J.; Mark Harper, C.; ,; Hughes, Natasha; de las Casas, Ruth; Long, Charlotte; Skeoch, Chris; Duckham, Emily; et al.
Highlights: Maternal thermal dysregulation is common after emergency caesarean section. The prevalence of hypothermia is as high as 15%. The prevalence of hyperthermia after emergency caesarean section is as high as 20%. The mode of anaesthesia is associated with thermal dysregulation. Maternal heat loss is common in the peri-operative period. Abstract: Background: Temperature regulation in women undergoing emergency caesarean section is a complex topic about which there is a paucity of evidence-based recommendations. The adverse effects of inadvertent peri-operative hypothermia are well described. Hyperthermia is also associated with adverse neonatal outcomes, an increased risk of obstetric intervention and increased treatment for suspected sepsis. We conducted a multi-centre observational cohort study to identify the prevalence of hypothermia and hyperthermia during emergency caesarean section. s: Participants undergoing emergency caesarean section were recruited across 14 sites in the UK. The primary end point was maternal temperature in the recovery room. Temperature was measured using a zero heat-flux temperature monitoring device. Results: Two hundred and sixty-five participants were recruited over a 12-month period. The prevalence of hypothermia (<36.0°C) was 10.7% and the prevalence of hyperthermia (>37.5°C) was 14.7% on admission to recovery. The prevalence of hypothermia, normothermia, and hyperthermia differed among type of anaesthesia: 71.4% of the hypothermic group had received a spinal anaesthetic whereas 76.9% of the hyperthermic group had received epidural top-up anaesthesia. There was a significant decrease in maternal temperature between the time of delivery and admission to the recovery room of 0.20°C (95% CI 0.15 to 0.25, P <0.001). Conclusions: Both hypothermia and hyperthermia are prevalent findings in mothers who undergo emergency caesarean section. Therefore, accurate temperature measurement is essential to ensure that an appropriate intra-operative temperature management strategy is employed.